Transformasi Nilai Silaturahmi dalam Era Digital: Telaah Kontekstual Perspektif Islam - Dwi Harjana; Ahmad Khairul Fajri; Sheila Aprianti; Abdul Halim Talli (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to examine the transformation of the value of silaturahmi (social bonding) in the digital era from an Islamic perspective. Silaturahmi, as a fundamental teaching in Islam, encompasses deep spiritual, social, and moral dimensions. Amidst technological advancements and shifting patterns of social interaction, the practice of silaturahmi has evolved from direct physical contact to virtual communication. This research employs a qualitative approach with contextual analysis of normative Islamic sources and contemporary social phenomena. The findings indicate that although the form of silaturahmi has changed, its essence remains intact as long as the core principles of Islamic ethics—such as sincere intention, compassion, and mutual respect—are upheld. Digital media, including instant messaging and social platforms, can serve as legitimate and effective tools for strengthening interpersonal relationships when used ethically and responsibly. Therefore, silaturahmi remains relevant and applicable in modern social life as part of preserving ukhuwah (brotherhood) and communal harmony.